Biology of Hevea Rubber - Priyadarshan, P.M (CABI, 2014)
Rubber is an elastic substance obtained from the exudates of certain tropical plants (natural rubber) or derived from petroleum and natural gas (synthetic rubber). Because of its elasticity, resilience and toughness (Table 1.1), rubber is the basic constituent of tyres used in automotive vehicles, aircraft and bicycles. The same properties make it useful for machine belting and hoses of all kinds. Rubber is also used in electrical insulation, and, because it is waterproof, it is a favoured material for shoe soles. From mere rubber bands to catheters, condoms and latex threads, rubber makes more than 50,000 products. A car has almost 30% of its components made of rubber. Natural rubber is produced from over 7500 plant species (Compagnon, 1986), conﬁ ned to 300 genera of seven families, namely the Euphorbiaceae, Apocynaceae, Asclepiadaceae, Asteraceae, Moraceae, Papaveraceae and Sapo- taceae (Archer and Audley, 1973; Heywood, 1978; Backhaus, 1985; Lewinsohn, 1991; John, 1992; Cornish et al., 1993) (Table 1.2). At least two fungal species are also known to make natural rubber (Stewart et al., 1955). Hevea brasiliensis (Willd. Ex. A. de. Juss. Müll-Arg.) is the almost exclusive contributor towards natural rubber produced worldwide (Greek, 1991). Hevea trees descended from seedlings transplanted from Brazil to South and South-east Asia that have under- gone several cycles of breeding are now the prime source of the modern world’s natural rubber. Natural rubber is produced in South-east Asia (92%), Africa (6%) and Latin America (2%). The main producing countries are (by descending order): Thailand (3.09 million t in 2008), Indonesia, Malaysia, India, China, Vietnam, and also Sri Lanka, Brazil, Liberia, Côte d’Ivoire, the Philippines, Cameroon, Nigeria, Cambodia, Guatemala, Myanmar, Ghana, Democratic Republic of Congo, Gabon and Papua New Guinea.